2020
DOI: 10.48550/arxiv.2012.05598
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Amodal Segmentation Based on Visible Region Segmentation and Shape Prior

Abstract: Almost all existing amodal segmentation methods make the inferences of occluded regions by using features corresponding to the whole image. This is against the human's amodal perception, where human uses the visible part and the shape prior knowledge of the target to infer the occluded region. To mimic the behavior of human and solve the ambiguity in the learning, we propose a framework, it firstly estimates a coarse visible mask and a coarse amodal mask. Then based on the coarse prediction, our model infers t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
(4 reference statements)
0
1
0
Order By: Relevance
“…To mimic this amodal perception ability, amodal instance segmentation [26] has been proposed, in which the goal is to segment both the amodal and visible masks of each object instance in an image. The SOTA approaches are mainly built on visible instance segmentation [27], [28] and perform amodal segmentation through the addition of an amodal module, such as amodal branch and invisible mask loss [29], multi-level coding (MLC) [30], refinement layers [31], and occluder segmentation [32]. They have demonstrated that it is possible to segment the amodal masks of occluded objects on various datasets [29], [30].…”
Section: Related Workmentioning
confidence: 99%
“…To mimic this amodal perception ability, amodal instance segmentation [26] has been proposed, in which the goal is to segment both the amodal and visible masks of each object instance in an image. The SOTA approaches are mainly built on visible instance segmentation [27], [28] and perform amodal segmentation through the addition of an amodal module, such as amodal branch and invisible mask loss [29], multi-level coding (MLC) [30], refinement layers [31], and occluder segmentation [32]. They have demonstrated that it is possible to segment the amodal masks of occluded objects on various datasets [29], [30].…”
Section: Related Workmentioning
confidence: 99%